PERAN MUSYAWARAH PERENCANAAN PEMBANGUNAN DALAM PERENCANAAN PEMBANGUNAN DAN TATA KELOLA PEREKONOMIAN DESA - Harsanti, Tikka Dessy; Lilasari, Yuta (PANGRIPTA, 2019)
This study aims to analyze the processes and processes that occur in development planning in Pulungdowo Village, the role of the community in the development planning process, the process of controlling or controlling the use and financial management through the village consultative body, the development process of the economic development process. From the results of an analysis that can be reported on the process of development planning and financial management in Pulungdowo Village, has approved the mandate of Law Number 6 on Villages in 2014 by linking together the aspirations of the community and stakeholders in the village and its ranks in the village development planning consultation forum that supports the development of people welfare. To represent the results of this study, it is expected to produce consideration in generating synergy between the aspirations of the people and stakeholders or shareholders for better development in the village.